Análisis temporal y espacial de la calidad del aire determinada por el material particulado pm10 y pm2.5 en el parque industrial municipios de nobsa, corrales y Sogamoso (Boyacá) - Gil Serrano, Miguel Ángel; Tobo Paipilla, Julián Edgardo (Universidad Antonio Nariño, 2022)
This research focus on the time-space distribution of particle called PM10 and PM2.5 in the industrial park located in the municipalities of Nobsa, Corrales and Sogamoso in the Department of Boyacá. In order to evaluate the concentrations of particulate matter through the use of monthly historical data from monitoring stations in the area of influence taken from the SISAIRE portal installed by the autonomous corporation of Boyacá CORPOBOYACA in the period between 2019- 2021. For particulate material PM10, data was taken from 7 stations UPTC, HOSPITAL, SOGAMOSO-KOICA, SOGAMOSO-SENA, SOGAMOSO-RECREO, NOBSA-NAZARETH, NOBSA - BOMBEROS, while for particulate material PM2.5, 4 stations were taken SOGAMOSO - KOICA, SOGAMOSO-RECREO, NOBSA-NAZARETH, NOBSA-FIREFIGHTERS.